The Effect Analysis of Self Attitude and Efficacy on Entrepreneurship Intention of Economics Education Students, Universitas Riau - Lia Yusti Sakinah; Sri Kartiko; Syakdanur Nas (Journal of Educational Sciences, 2019)
Students are expected to be able to build the Indonesian to survive and win the increasingly fierce competition. Since many scholars are unemployed, this intense competition will be difficult to pass. This phenomenon is inseparable from the entrepreneurial intention factor. This study aims to analyze the influence of entrepreneurial attitudes and self-efficacy on entrepreneurial intentions in University Riau of Economics Education students. The populations in this research were 154 students of Economic Education in University Riau. The sampling technique used was Simple Random Sampling with the total of samples obtained were 105 students. The data collection used a questionnaire with the Likert scale. The data analysis technique in this study was Multiple Linear Regression with the supporting of SPSS. The results of this study indicate that attitudes and self-efficacy have a positive and significant effect on entrepreneurship intention in Economic Education students University Riau of 12.5%.